Answer:
![f(x) = \frac14(x + 1)^2(x + 3)(x -2)( x - 3)](https://img.qammunity.org/2023/formulas/mathematics/college/bc4bjl8rzkvhn3oe734zzibxv4plfig7d9.png)
Tia is correct
Explanation:
From inspection of the graph, we can say that the leading coefficient of the function is positive as:
![f(x) \rightarrow - \infty, \textsf { as } \ x \rightarrow - \infty\\f(x) \rightarrow +\infty, \textsf { as } \ x \rightarrow + \infty](https://img.qammunity.org/2023/formulas/mathematics/college/3v9u4kt4mbvt0tiw03gxla5hr340dlm2v1.png)
From inspection of the graph, we can see that the curve intercepts the x-axis at x = -3, x = 2, x = 3
As the curve touches the x-axis at (-1, 0) then this means that the root x = -1 has multiplicity 2
Therefore,
where
is some positive constant.
If we multiply the constants, we can determine the y-intercept:
y-intercept = a x 1² x 3 x -2 x -3 = 18a
Therefore, the y-intercept is at y = 18a
From inspection of the graph, the y-intercept is at y = 4.5
So to determine the value of a: 18a = 4.5 ⇒ a = 1/4
Therefore, the fully factored form of the equation is:
![f(x) = \frac14(x + 1)^2(x + 3)(x -2)( x - 3)](https://img.qammunity.org/2023/formulas/mathematics/college/bc4bjl8rzkvhn3oe734zzibxv4plfig7d9.png)